Kontribusi Pengembangan Sumber Daya Manusia dalam Upaya Meningkatan Mutu Pendidikan Madrasah Aliyah Al-Amiriyyah Banyuwangi - Nur Hidayati; Nayla Izza Kumala (Jurnal Manajemen Pendidikan Islam Darussalam (JMPID), 2020)
The purpose in this study are: (1) To find out how is human resources of Madrasah Aliyah al-Amiriyyah Blokagung Tegalsari Banyuwangi 2019/2020 academic year; (2) To find out how the education quality of Madrasah Aliyah Al-Amiriyyah Blokagung Tegalsari Banyuwangi 2019/2020 Academic Year; (3) To find out what are the factors that can improve the education quality of Madrasah Aliyah Al-Amiriyyah Blokagung Tegalsari Banyuwangi 2019/2020 Academic Year; (4) To realize the contribution of human resources development a which applied in improving the education quality of Madrasah Aliyah Al-Amiriyyah Blokagung Tegalsari Banyuwangi 2019/2020 Academic Year. This research method uses descriptive qualitative, data collection through interviews, observation and documentation. Data analysis uses interactive three models, while the data validity technique uses triangulation. Based on the clarification of inhibiting and supporting factors, the contribution of human resource development in improving the education quality of MA al-Amiriyyah Blokagung Tegalsari Banyuwangi can be explained as follows: (1) Teacher Training based on the respective fields of expertise held by the Religion Ministry. The human resources quality of educators and educational personnel is one of the factors in improving the quality of madrasas, by the qualified human resources quality, it is expected to produce cadres quality. (2) Direction from the Head of Education and Boarding School Caregiver, this briefing aims to provide motivation to educators and education staff.